Implementation of The Pulmonary Tuberculosis Control Program at Sikumana Public Health Center - Malehere, Eleta (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: According to the East Nusa Tenggara Provincial Health Office, Kupang City is the city with the highest contribution to pulmonary TB cases in 2021 with 491 cases and the Sikumana Health Center is the Public Health Center with the highest number of TB cases with 88 cases, patient recovery rate of 68.2%, and not reached the national target of 100%. The purpose of this study was to analyze the implementation of the pulmonary TB control program at the Sikumana Health Center. Methods : The research study was qualitative research using in-depth interview techniques. The number of informants was 11 informants. This research was conducted at the Sikumana Health Center, District Maulafa, City of Kupang from February to April 2023.Results: In the input aspect, the funds program, and human resources are sufficient, and the facilities for implementing the TB program are incomplete. In the process aspect, the planning and implementation stages have been going according to the proposed activity plan, but in the monitoring and supervision activities, it is still lacking because it is administrative and based on recording and reporting only. In the output aspect, the coverage of case detection in 2022 is 58.5%, the notification rate for all cases is 22.8%, the treatment success rate is 94.2%, and the cure rate is 98.2%.Conclusion: The Pulmonary Tuberculosis program implementation in Sikumana Health Center wasn’t implemented successfully because of process and input problems such as facilities and human resources. There should be regular training for TB program implementing officers, a special room for sputum collection, and routine supervision to the laboratory.